People Management and Neuroendocrine Balance: Development of the Occupational Biochemical Roadmap (ROBO) for Integrated Mental Health (Research, Society and Development, 2026)
This article aims to develop the Occupational Biochemical Roadmap (OBR), a protocol that translates the rigor of neuroscience into the practice of People Management. It is observed that mental health in the workplace faces increasing challenges due to chronic stress and disruption of the circadian rhythm, aggravated by hyperconnectivity and intense work demands. Traditional People Management models often neglect the physiological basis of resilience and performance. This study, through an integrative literature review, proposes to integrate neuroendocrine knowledge into People Management, focusing on key chemical messengers (hormones such as cortisol, melatonin, and oxytocin; neurotransmitters such as dopamine, serotonin, and GABA) that regulate relevant physiological axes: stress/adaptation, recovery/circadian rhythm, plasticity/cognition, and socio-emotional/vigor. The Occupational Biochemical Routine (OBR) was developed, a daily protocol based on consolidated scientific evidence, which includes practices such as active breaks for endorphin release and GABA/glutamate balance, and social interactions for oxytocin modulation. The OBR aims to optimize neuroendocrine resilience, promoting healthier and more productive workers, with organizational benefits. However, as a conceptual model, it requires future empirical validation through studies with biomarkers.